Digital and socioeconomic inequalities in perceived mobility restrictions for activity participation: Captive users in Madrid - Segundo Paico-Saavedra; Alberto Rojas-Rivero; Raúl F. Elizondo-Candanedo; Aldo Arranz-López; Julio A. Soria-Lara (Journal of Urban Mobility)
Although COVID-19′s impact on mobility has been widely studied—often highlighting the disproportionate burden on vulnerable groups—two aspects remain understudied: the need for a multidimensional approach to vulnerability, and the role of perceived rather than observed mobility restrictions in shaping access during crises. This study addresses this gap by investigating how structural vulnerabilities (e.g., transport mobility, digital access, and socioeconomic) shaped the ability to engage in work and educational activities during the COVID-19 pandemic in the Madrid Region. A survey of captive public transport users was conducted, and Principal Component Analysis (PCA) was used to identify key dimensions of vulnerability. These dimensions -related to socioeconomic status, digital access, household characteristics, and commuting conditions- were then included in an ordinal logistic regression to assess their influence on perceived mobility difficulty. The results reveal a complex and layered geography of vulnerability. Individuals with limited teleworking capacity, digital exclusion, and economic precarity were significantly more likely to report mobility restrictions, especially in suburban and peripheral areas with fewer transport alternatives. In contrast, those with greater digital access, financial resilience, or private mobility options reported fewer barriers. The findings emphasize that transport-related disadvantages cannot be understood without digital and social inequalities. Policy implications include the need to integrate digital accessibility into transport equity frameworks, improve service provision in structurally dependent areas, and recognize informal household-level mobility strategies as assets.